Optimizing Magnesium Composites with Zirconia Using Response Surface Methodology - D. Jayakumar; Dr. D. Balaji (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Magnesium composites reinforced with micro Zirconia particles offer significant potential for enhanced performance in various engineering applications due to their improved mechanical properties. This study focuses on optimizing the mechanical performance of such composites using Response Surface Methodology (RSM). The composites were prepared through Liquid Metallurgy, specifically using the Stir Casting Process, with a reinforcement level of 5% weight percentage (wt.) of Zirconia. The primary objective of this research was to evaluate the impact of Zirconia reinforcement on the mechanical properties of Magnesium composites, including tensile strength, hardness, and impact strength. Pure Magnesium and Magnesium composites with 5% Zirconia were subjected to a series of laboratory tests to measure these properties. The data collected were analyzed to assess the improvements in mechanical performance attributed to the Zirconia reinforcement. Response Surface Methodology was employed to optimize the reinforcement parameters and predict the performance of the composites. This approach allowed for a comprehensive analysis of how variations in the reinforcement levels influence the mechanical characteristics of the composites. The findings indicate that the addition of Zirconia significantly enhances the tensile strength, hardness, and impact strength of Magnesium composites, demonstrating the effectiveness of Zirconia as a reinforcement material. The results from this study provide valuable insights into the optimization of Magnesium-Zirconia composites, offering guidance for future research and development in the field of advanced materials. The optimized composites show promise for applications requiring high-strength, durable, and impact-resistant materials, contributing to the advancement of Magnesium-based engineering solutions.